PENGARUH PELATIHAN ONLINE TERHADAP KINERJA KARYAWAN PADA PT. TUNASKARYA INDOSWASTA - Soehardi, Dwi Vita Lestari; ., Satriadi; Kusumah, Surya (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2022)
Human Resources is an important property by a company. Having a high performance, attitude and motivation from human resources will support the main goals of the company. Achieving the company's main goals will enable the company to survive amid the high minimum wages in Indonesia, especially at PT. Tunaskarya Indoswasta. The main objective of this research is to find out that online training has a significant effect on the performance of employees at PT. Tunaskarya Indoswasta even partially or simultaneously. The population in this study were all employees of the production section of PT. Tunaskarya Indoswasta, amounting to 147 people, from this population the researcher will choose a sample that is used as a respondent in this study. Then the researchers used a simple random sample in this study. By using the Slovin formula, the researcher obtained a sample of 108 people. The data collection method uses an answer sheet. Data analysis used simple linear regression with the help of SPSS software. The results showed that online training had an effect on employee performance while the percentage of the coefficient of determination (R2) was 25.30%. This means that performance is influenced by online training 25.30%, while others are influenced by other variables disclosed.